EFEKTIFITAS PELAKSANAAN MAGANG INDUSTRI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN - Samidjo Samidjo (Jurnal Taman Vokasi, 2017)
The aim of the researh was to describe the effectiveness of  industrial appreticeship program of mechanical engineering education students, the  Education and Teacher Training Faculty of Sarjanawiyata Tamansiswa Yogyakarta. The research was a qualitative approach research. To measure the effectiveness of the apprenticeship program the research used CIPP  (context, input, process, product) model introduced by Stuflebeam. The data of the research was collected by using interview and observation method, and completed by documentation. From the context side, the goal of the apprenticeship can fullfil the hope of industry to answer the lack of competencies of the vocational school teacher candidates, while from the input side, the the strategy implemented by the management in finding and selecting the industry by the students  can not assure the feasibility of the industry for apprenticeship.  From the process side, due to the budgetary, the gude lines as prescribed in the guide book are not fully implemented, the lecturers as the conselor can not perform as prescribe in the guide book. From the product side, in general the apprentisechip can be categorized as effective, the students doing their work mostly more than 256 hours as prescribed in the regulation. The subject of the apprenticeship focus are  the management and the skill relevance to the concentration of the students, the skill reletaed to the concentration can be categorized as effctice, but on the management side, the apprenticeship can be categorized as not effective. Ther is no one of the student learning the management of the company in the industry the students doing apprenticeship.